Urethral pressure variation: a neglected contributing factor in patients with overactive bladder syndrome? - Kirschner-Hermanns,Ruth (2017)
ABSTRACT Objective To study urethral pressure variations during the whole filling phase among different groups of patients. Material and Methods We investigated 79 consecutive patients from January 2011 to June 2012. All patients were recruited within our routine practice in our continence clinic and were evaluated with urodynamic exam according to the standards of the International Continence Society (ICS) with an additional continuous measurement of the urethral pressure profile (cUPP) that was done in a supine position. Patients with genital prolapse >grade I, as well as patients with impaired cognitive function or neurogenic disorders were excluded. Bacteriuria at the time of investigation was excluded by urine analysis. Urethral pressure changes higher than 15cmH2O were considered as ‘urethral instability’. Results From 79 investigated patients, 29 were clinically diagnosed with OAB syndrome, 19 with stress urinary incontinence (SUI) and 31 with mixed (OAB and SUI) incontinence. The prevalence of ‘urethral instability’ as defined in this study was 54.4% (43/79). The mean Δp in patients with OAB (36.5cmH2O) was significantly higher (p<0.05) than in groups with pure stress (14.9cmH2O) and mixed urinary incontinence (19.3cmH2O). Conclusions Etiology of ‘urethral instability’ is unknown, but high prevalence among patients with overactive bladder syndrome, especially concomitant with detrusor activity can raise a fair question and direct further diagnostic as well as treatment efforts.